PENGARUH TAX AVOIDANCE DAN MEKANISME INTERNAL TATA KELOLA PERUSAHAAN TERHADAP AUDIT REPORT LAG - CHRISTIAN SHANDY PUTRA S.; HERY GUNAWAN (E-Jurnal Manajemen Trisakti School of Management (TSM), 2026)
The purpose of this research is to obtain the empirical evidence about the effect of the tax avoidance, audit committee size, audit committee expertise, audit committee diligence, board size, board independence, and board diligence as an independent variable that take refer to audit report lag as a dependent variable. The population of this research are manufacturing companies that listed in the Indonesia Stock Exchange (BEI) from 2021 to 2023. The sample used for this research consist of 81 companies, the selection process of these sample used the purposive sampling method with 243 total data and the data analysis method in this research using multiple regression analysis. The result in this research indicates that board size have a significant effect to audit report lag. Meanwhile tax avoidance, audit committee size, audit committee expertise, audit committee diligence, board independence, and board diligence didn’t have a significant effect to audit report lag.